2020
DOI: 10.1111/jcal.12449
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing community of inquiry and reflective thinking skills of undergraduates through using learning analytics‐based process feedback

Abstract: This research aims to investigate into the effect of using learning analytics (LA)-based process feedback on students' perceptions of community of inquiry (teaching, social and cognitive presence) and their reflective thinking skills. By using a mixed-method research approach (QUAN + qual), this study was conducted as an experimental design with the pretest-posttest control group. A total of 104 university students who were randomly assigned to the experiment group (EG) and control group (CG) were recruited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 44 publications
(55 reference statements)
1
19
0
1
Order By: Relevance
“…The literature records many attempts to improve learners' engagement and cognitive presence on the LMS platform (Yilmaz, 2020). This research adds to the literature library a new tool for improving the student intention to continue using the LMS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The literature records many attempts to improve learners' engagement and cognitive presence on the LMS platform (Yilmaz, 2020). This research adds to the literature library a new tool for improving the student intention to continue using the LMS.…”
Section: Discussionmentioning
confidence: 97%
“…The level of use can be measured by actual use or through the intention to continue using the application in the future (Hong et al, 2017). Thus, to improve learners' engagement various academic attempts have been made, such as learning analytics (Yilmaz, 2020) and a personalised recommendation system (Yilmaz & Yilmaz, 2020). However, these significant research attempts focused mainly on the current use and the current benefits of the LMS, rather than seeking to explain the variation in the intention to continue using the LMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the study, they conducted to determine the impact of learners' interactions on their learning performances by using learning analytics in the online environment; Agudo-Peregrina et al (2014) found out that there was a relationship in positive direction between the two variables. The study by Yilmaz (2020) found that learning analyticsassisted feedback not only made the online learning environment more effective but also promoted the online activities to be more meaningful and enabled students to be more involved in these activities. When the results obtained from the present study and the results obtained in the literature are evaluated together, it has been determined that similar findings have been Learning analytics reached indicating that learning analytics give the instructor the opportunity for an early intervention.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…The recent advancements in the field of computing have enabled educators and practitioners to increase the effectiveness of instructional design and allowed them to collect and analyze large-scale digital datasets. One proposed solution to investigate and explore such topics involves the collection and interpretation of so-called 'big data', which are processed with the aid of machine learning (ML) models and educational data mining (EDM) techniques [6][7][8]. The so-called learning analytics (LA) discipline is an emerging field, with rapid growth over the last five years, which aims at assisting researchers and instructors to better understand learners' needs by collecting and interpreting large-scale data in a systematic and independent way.…”
Section: Introductionmentioning
confidence: 99%